Describing and classifying coach development programmes: A synthesis of empirical research and applied practice - Lefebvre, J. S.; Evans, M. B.; Turnnidge, J.; Gainforth, H. L.; Côté, J. (International Journal of Sports Science & Coaching, 2016)
Coach development, coach development programmes are conducted to change coach behavior in a specific domain. To facilitate understanding of this growing field, the current synthesis review of coaching literature was conducted to generate classifications of coach development programme types. To identify coach development programmes described within academic research, a supplemental search of an earlier systematic review was conducted. In addition, a broad Internet search was used to identify publically available descriptions of coach development programmes. After extracting information describing the resulting 285 coach development programmes, the research team distinguished 16 coach development programme domains of focus, classified within professional, interpersonal, or intrapersonal domains. Five organizational contexts were also identified in relation to "where" and "why" coach development programmes were conducted, and the coaching context and mode of delivery were also classified. As an effort to bridge applied and empirical realms, the continued use and development of these classifications will facilitate the further progress and synthesis of coach development literature. ABSTRACT FROM AUTHOR